Unusual optical centres in fancy brown diamonds - A. I. Dorofeeva; S. V. Titkov (Известия высших учебных заведений: Геология и разведка, 2021)
Background. Natural brown diamonds with fancy yellow, orange, red and green tints are valuable jewelry raw materials. Their colour is associated with post-crystallisation plastic deformation occurring during transportation from the mantle to the Earth’s surface.Aim. To study point defects in plastically deformed diamonds using optical and IR spectroscopy.Materials and methods. Faceted brown diamonds with fancy tints presented on the Russian market were studied spectroscopically. Selected samples were examined using UV-visible optical absorption spectroscopy and IR spectroscopy.Results. We discovered unusual optical centres in the absorption spectra of the UV-visible region. In addition, the known continuous absorption increasing from the red to the ultraviolet region of the spectrum, as well as the N3 and H3 nitrogen centres and a band at 550 nm, were revealed. In the spectra of yellowish-brown diamonds, the bands at 512.9 nm and 519.9 nm and an accompanying broad band with a maximum of 480 nm were found. The appearance of a yellowish tint of crystals was associated with these optical centres. The bands 506.5 nm, 516.1 nm and 679.7 nm were established in the spectrum of orange-brown diamond samples. An additional absorption continuum associated with single nitrogen atoms and centres (NV)– were observed in greenish-brown diamond samples. Their simultaneous presence causes the appearance of a greenish tint in the diamond colour.Conclusion. The information obtained using IR spectroscopy indicates that an intense brown colour can occur not only in the most common Ia type crystals according to the physical classification of diamonds, but also in relatively rare Ib + IaA type diamonds.